Analisis Tingkat Kemandirian Karang Taruna Pada Kemampuannya Dalam Perawatan Kendaraan Motor - Anes Inda Rabbika; Mia Sumiarsih; Muhammad Hanhan Nugraha; Widyantoro; Rachmanto Hadiputranto (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
The more villager have motorcycle, the more routine maintanance is needed. If the activity villager is high, so there is no chance to go to maintenance workshop because the place is far from village . the result of observation, during trip from village to city there is no a maintenance workshop, and if damage was found on the trip there is no solution except pushed the motorbike to find a maintanance workshop. the best solution for this problem is training ability self to maintain motorcycle by villager.the result of research are : 1) 4 indicators of the motorcycle maintenance karang taruna independence is positif2) Based of this research, The dominan indicator is having a strong desire to develop themselvesthe research method's used is questionnaire, Interview and observation. questionnaire data processing using likert scale.